Fundamentals and history of implant dentistry - Tamal Kanti Pal (Wolters Kluwer Medknow Publications, 2015)
The practice of implant dentistry was not there a few decades ago It has its long historical retrospectives. The quest for rehabilitation of edentulous ridge has intrigued mankind since ancient times. The period from the time of Egyptian and Mayan civilizations to 1930s was unique when clinicians attempted to replace a missing tooth utilizing various materials. The spark of inquiry began from mid-1930s with the advent of an alloy named "vitallium;" attempts have been made to utilize this new material as an implant. Thereafter, in early 1950s, a good deal of fundamental and clinical research started taking place. These research data had given a boost to the tremendous growth of the practice of using dental implants made of vitallium that practically exploded to reach every general practitioner's clinic across the globe. Critical understanding of bone physiology, drilling protocol, implant design and surface texture, initial implant stability, single-stage implant surgery, and immediate loading of implants are the few factors based on which modern implant practice has become a predictable treatment modality for the replacement of missing teeth.